Testing short-term over/ underreaction hypothesis: empirical evidence from the Egyptian stock exchange - Ragab, Amira Yasser (AUC Knowledge Fountain, 2014)
The overreaction hypothesis, as postulated by De Bondt and Thaler (1985) dictates that “stocks that have performed poorly in the past (loser stocks) tend to outperform stocks that have performed well in the past (winner stocks)" (DeBondt, et al., 1985). On the other hand, the under-reaction hypothesis argues that stock's return shows momentum, whereby winner stocks continue to exhibit high returns in future periods, reflecting tendency of investors to under-weigh the extent of new information. The aim of this thesis is to investigate whether short-term overreaction or under-reaction appears in the Egyptian Exchange (EGX) over the period of January 1998 to December 2013, making this the first attempt to test these market anomalies in an Arab stock market. The thesis surveys the overreaction/under-reaction literature focusing on the differences in methodologies and results across the various sample markets and timeframes. The thesis compares two standard methodologies in the literature, that of Ali et al (2011) and Clare & Thomas (1995), to test the overreaction/under-reaction hypothesis over various holding periods ranging from one week to 52 weeks. The analysis reveals that while short-term overreaction doesn't exist in the Egyptian Exchange, there is statistically significant evidence of under-reaction for the holding periods of one to four weeks. This motivates further tests to establish the profitability of utilizing this evidence of under-reaction by applying a momentum strategy that invests in winner stocks. The results show that while a momentum strategy can provide significant abnormal returns of up to 0.885% over a holding period of four weeks, when trading costs are taken into account, the profitability of the momentum strategy becomes insignificant. The thesis further analyzes whether size of the company can explain the evidence of under-reaction. This is done on the basis of creating portfolios with large and small capitalization stocks. For large capitalization stocks, an under-reaction that is statistically significant over holding periods from 1 to 3 weeks is found. The overall result for this thesis suggests that while evidence of under-reaction appears for Egyptian listed stocks, this is concentrated in large firms. Investor, however, cannot profit from this market anomaly by applying a momentum strategy since after taking into account trading costs involved in trading Egyptian stocks, the profitability of this strategy diminishes.